Neutron activation resonance integrals of 64Zn, 68Zn, 85Rb, 100Mo, 102Ru, 113In, 123Sb, and 180Hf - Ricabarra, M. D.; Turjanski, R.; Ricabarra, G. H. (The National Research Council of Canada, 1969)
Fil: Ricabarra, M. D. Comisión Nacional de Energía Atómica; Argentina